2018
DOI: 10.1139/er-2017-0096
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of imidazolinone herbicide and Clearfield® rice between weedy rice—control efficiency and environmental concerns

Abstract: Water scarcity and increasing labor costs of rice cultivation have prompted many agro-ecosystems in the world to adopt the direct-seeded rice (DSR) method instead of the hand-transplanting method. However, there is a downside to this approach, which is the prevalence and spread of weedy rice (WR), a troublesome weed in paddy fields that has the potential to cause a 90% loss of total yield in high-infested areas. The progression, infestation, and dynamics of WR are linked to environmental circumstances, types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 142 publications
(167 reference statements)
0
14
0
Order By: Relevance
“…Herbicide carryover from the implementation of CPS is another major concern and challenge ( Bajrai et al 2017;Mahyoub et al 2017;Bzour et al 2018). The carryover of imidazolinone was reported to affect many non-rice crops in rotational systems (Allister and Kogan, 2005;Bahm et al 2011).…”
Section: -120 D After Sowing Harvestingmentioning
confidence: 99%
See 2 more Smart Citations
“…Herbicide carryover from the implementation of CPS is another major concern and challenge ( Bajrai et al 2017;Mahyoub et al 2017;Bzour et al 2018). The carryover of imidazolinone was reported to affect many non-rice crops in rotational systems (Allister and Kogan, 2005;Bahm et al 2011).…”
Section: -120 D After Sowing Harvestingmentioning
confidence: 99%
“…The carryover of imidazolinone was reported to affect many non-rice crops in rotational systems (Allister and Kogan, 2005;Bahm et al 2011). Imidazolinone residues in the soil were already detected in Malaysia rice field (Bajrai et al 2017;Mahyoub et al 2017) which could potentially impact non-IMI rice cultivars in CPS rotation system (Bzour et al 2018). Proper and organized studies, researches and surveys of imidazolinone carryover in CPS rice fields in Malaysia need to be orchestrated by various organizations and institutions to reduce the herbicidal impact to human and environment (Bzour et al 2018).…”
Section: -120 D After Sowing Harvestingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these benefits have encouraged the use of this technology continuously and, as a consequence, imidazolinone-resistant (IMI-R) red rice was identified in commercial rice fields just a few seasons after CL rice was released in the USA (Zhang et al, 2006;Ellstrand, 2018), Brazil (Menezes et al, 2009), Italy (Busconi et al, 2012), and other regions of Europe and Latin America (Ziska et al, 2015). In addition to the herbicide selection pressure, the gene flow from CL rice to red rice escapees has contributed to the IMI-R red rice evolution (Goulart et al, 2012;Bzour et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hands the farm areas are being lessen by residential areas in the developing countries. Previous experiments showed that the production rate of rice is unpleasantly affected by abiotic stress and that is highly defenseless with the change of weather [5,6,19,3]. Various Modern biotechnological tools requires the optimization of an efficient regeneration protocol for specific cultivar(s) is an essential for the composition of the nutrient media is a major factor that influencing the regeneration frequency of rice [2].…”
Section: Introductionmentioning
confidence: 99%